Análise tridimensional do espaço aéreo faríngeo e do osso hióide de pacientes submetidos à cirurgia ortognática - Yamashita, Amanda Lury (2015)
The aim of this study was to analyze the displacement of the hyoid bone and the volume change of the pharyngeal airway space (PAS) after orthognathic surgery using cone-beam computed tomography (CBCT). Methods: 30 patients were divided into: group 1 - patients undergone maxillary advancement and mandibular setback (n=15) and group 2 - patients undergone maxillomandibular advancement (n=15). CBCT scans were taken at three stages: T0 (before surgery), T1 (average of 1.5 months postoperatively), and T2 (average of 6.7 months postoperatively) and analyzed at Dolphin Imaging & Management Solutions? 3D version 11.7 software. For statistical analysis, we used ANOVA followed by Tukey test. In the hyoid bone, there wasn?t statistically significant difference between groups and times. There was significant difference between groups in change of the total volume (p=0.0334) and the minimum axial area (p=0.0446). For the lower volume, there was a significant difference between groups (p=0.0022) and between times (p=0.0254), with significant difference between the preoperative and the late postoperative (p=0.0088). In maxillomandibular advancement and maxillary advancement with mandibular setback surgery, there was a significant difference in the volume of the PAS, but there wasn?t significant change in the hyoid bone position.